Frequency based spell checking and rule based grammar checking - Singh, Shashi Pal; Kumar, Ajai; Singh, Lenali; Bhargava, Mahesh; Goyal, Kritika; Sharma, Bhanu (2016 International Conference on Electrical, Electronics, and Optimization Techniques (ICEEOT), 2016)
English is a language that is spoken by around 380-420 million people on this planet and understanding it is not at all easy. The meaning of a sentence varies according to the context and the tone of the speaker. To convey the thoughts efficiently, the knowledge of the language and its various rules is very important as thoughts take the form of words and the words take the form of action. One should aim to minimize the errors while using the language. Lesser is the number of mistakes, better will be the communication. To aid in achieving this goal, we are creating a frequency based spell checker and a rule based grammar checker for English language. The grammar checker focuses on detecting and correcting tense related mistakes.